WORK FROM HOME (WFH) DAN PEMBENTUKAN KECERDASAN MORAL ANAK DI ERA PANDEMI COVID 19 - Mayana Ratih Permatasari (Wahana Islamika: Jurnal Studi Keislaman, 2020)
This study aims to critically analyze how the work from home carried out by parents during the covid 19 pandemics has an impact on the formation of children’s moral intelligence. This research is library research because it explores more of the contents and concepts contained in books. The research method used is a descriptive method with a content analysis approach. In general, the impact of work from home on the formation of children’s moral intelligence can be divided into two, namely negative and positive impacts. A negative impact occurs when parents fail to interact and care for and educate the children with good moral intelligence because they have burdened with a lot of office work. While the positive impact occurs when parents succeed in playing their role as educators, caregivers and mentors of children during work from home properly.